تقييم فعالية علاج وحمة قربة النبيذ بالليزر الصباغي النابض 585 نانومتر - خدام جمال (Latakia University Journal -Medical Sciences Series, 2017)
ضمت الدراسة 32 مريضاً يعانون من وحمة قربة النبيذ ، خضع كل منهم إلى 4 جلسات علاجية بفاصل 8 أسابيع بالليزر الصباغــي النابض 585 ن م مع جهاز تبريد هوائــي, بزمن نبضة 0.5 مل ثا، وقطر شعاع ليزري ثــابت 7 ملم مع مجــال تدفق طاقة ليزرية يتراوح بين 5- 6.5 جول / سم2 . أظهرت النتائج تحسناً في لون الوحمات عند تكرار الجلسات العلاجية، وبعد الجلسة الرابعة كانت درجة التحسن جيدة أو ممتازة عند 69% من المرضى. لوحظ ظهور فرفرية عابرة مترافقة مع ألم محتمل بعد كل جلسة مباشرة عند 87.5% ، تقشر عند 25% ، نقص التصبغ عند 9% ، فرط التصبغ عند 6%. وكانت كلها خفيفة ولم يزداد حدوثها مع تكرار الجلسات العلاجية. لقد بينت نتائج هذه الدراسة أن الليزر الصباغي النابض بطول موجة 585 ن م فعال في معالجة وحمات قربة النبيذ. Thirty-two patients with port-wine stain were included in this study. The 585 nm pulsed dye laser treatment with an air cooling device was repeated 4 times at 8 – week intervals with a setting of 0.5 ms pulse duration and an average energy fluence 5 - 6.5 J/ cm2, using 7 mm spot size. The results revealed improvement of port-wine stains after multiple treatments , and 69% of the patients achieved good or excellent clearance after the fourth treatment. Transient purpura and tolerable pain were noted immediately after each treatment (87.5%), crusting (25%), hypopigmentation (9%), hyperpigmentation (6%) were also mild and their occurrence didn’t increase by repeating treatment. The results of this study indicated that the 585 nm PDL is effective and well tolerated in the treatment of port wine stain